Bridging disciplines - Brookes, Alan (2002)
Puente en AUckland, Nueva Zelanda, por el arq. Marijke de Goey
Keywords: NUEVA ZELANDA; DE GOEY, MARIJKE; AUCKLAND; PUENTES; PUENTES PEATONALES; CONSTRUCCION; ESTRUCTURAS; ESTRUCTURAS RETICULARES ESPACIALES; ACERO